A method for preparing a sodium alginate-based gradient hydrogel sensor

By using materials such as sodium alginate and MXene, sodium alginate-based gradient hydrogels are prepared using oxidative ring-opening and layer-by-layer polymerization strategies, the problems of complexity and insufficient performance of existing hydrogel sensor preparation methods are solved, and the effects of high sensitivity and wide monitoring range are achieved.

CN119431693BActive Publication Date: 2025-04-22QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510037858.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-22
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing hydrogel sensors with gradient structures are complex in preparation methods, and their monitoring range and sensitivity still need to be improved, making it difficult to meet the application needs of high sensitivity and wide monitoring range.

Method used

Using sodium alginate (SA) as the hydrogel matrix material, a simple and efficient method for preparing gradient hydrogels was developed through oxidation of open ring-opening sodium alginate and layer-by-layer polymerization strategies, forming a high-modulus tough layer and a low-modulus elastic layer. Combining MXene as a conductive material, the structure and performance of the hydrogel were optimized.

Benefits of technology

The obtained sodium alginate-based gradient hydrogel has high sensitivity, wide monitoring range and good mechanical stability, which can effectively solve the inherent conflict between hydrogels in a wide detection range and high sensitivity, and expand its application potential and field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431693B_ABST
    Figure CN119431693B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of functional materials and polymer compound chemical processing, and relates to a method for preparing a sodium alginate-based gradient hydrogel sensor. The present invention first uses MXene as a conductive material to give the hydrogel excellent conductive properties; then SA and acrylamide are cross-linked under the initiation of ammonium persulfate to form a high modulus tough layer. Finally, the C2-C3 bond is selectively cut by APS to reduce the rigidity of the SA chain. At the same time, APS oxidizes the hydroxyl groups on the SA main chain into aldehyde groups and carboxyl groups, promotes the cross-linking of the modified SA and AM, and forms a low modulus elastic layer. The gradient structure hydrogel prepared by the present invention can be used for mechanical sensors, while achieving a wide detection range and high sensitivity, and having stable and excellent output performance, and can be used to prepare flexible wearable electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical processing of functional materials and polymer compounds, and relates to a method for preparing a sodium alginate-based gradient hydrogel sensor. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the diversification of application scenarios of smart devices, the application prospects of multifunctional wearable devices in human motion monitoring, disease diagnosis and electronic skin have attracted much attention. At present, the research on hydrogel sensors mainly focuses on its functional expansion, such as increasing or optimizing its antifreeze, self-healing, adhesion, etc. These studies have improved the application potential of hydrogels to a certain extent. However, limited by its uniform structure, it is still difficult to meet the application requirements of hydrogel sensors for high sensitivity and wide monitoring range. Inspired by the structure of human skin, the design of hydrogels with gradient structures has received special attention. Generally, gradient hydrogels with skin-like structures have mechanical properties close to those of skin, a wide monitoring range and high sensitivity. By regulating the structural parameters of gradient hydrogels (such as composition, pore size and conductive medium distribution, etc.), the properties of hydrogels can be well regulated to meet different application requirements.

[0004] However, the current preparation methods of hydrogels with gradient structures are complex, and the monitoring range and sensitivity still need to be improved. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a sodium alginate-based gradient hydrogel sensor. Inspired by the gradient structure of human skin, the present invention adopts biocompatible sodium alginate (SA) as the hydrogel matrix material, and develops a simple and efficient method for preparing gradient hydrogels by oxidative ring-opening sodium alginate and layer-by-layer polymerization strategy. The obtained hydrogel has high sensitivity, wide monitoring range and good mechanical stability. The specific steps are as follows: In the first step, SA and acrylamide (AM) are cross-linked under the initiation of ammonium persulfate (APS) to form a tough layer with high modulus. In the second step, APS selectively cuts the C2-C3 bond to reduce the stiffness of the SA chain. At the same time, APS oxidizes the hydroxyl groups on the SA main chain into aldehyde groups and carboxyl groups, promotes the cross-linking of the modified SA and AM, and forms a low modulus elastic layer. The gradient structure hydrogel prepared by the present invention can be used for mechanical sensors, while achieving a wide detection range and high sensitivity.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention provides a method for preparing a sodium alginate-based gradient hydrogel sensor, comprising:

[0008] The MXene dispersion was mixed evenly with a tannic acid (TA) aqueous solution to obtain a TA@MXene suspension;

[0009] Sodium alginate and acrylamide are dissolved in a solvent, added into the TA@MXene suspension and mixed evenly, and a polymerization reaction is carried out in the presence of an initiator and a cross-linking agent to obtain a tough layer with a high modulus.

[0010] allowing sodium alginate and ammonium persulfate to react in a solution to obtain an oxidatively modified sodium alginate solution;

[0011] The oxidatively modified sodium alginate solution is uniformly mixed with acrylamide, water, a crosslinking agent and a TA@MXene suspension to obtain an elastic layer hydrogel precursor solution;

[0012] The elastic layer hydrogel precursor solution is placed on the high modulus tough layer and allowed to stand to obtain a sodium alginate-based gradient hydrogel sensor.

[0013] The present invention uses bio-based sodium alginate as a raw material for hydrogel synthesis, and performs ring-opening modification on the basic structural unit of sodium alginate by chemical method to prepare a hydrogel material with a gradient pore structure, and the hydrogel can produce high sensitivity and a wide range of dynamic responses to external mechanical stimulation. Therefore, the present invention is of great significance for improving the application potential of hydrogel and expanding its application field.

[0014] The present invention uses MXene as a conductive material to give the hydrogel excellent conductive properties. Therefore, the present invention studies the dosage of MXene. Preferably, in the TA@MXene suspension, the mass ratio of MXene to tannic acid is 10:4-5.

[0015] The present invention forms a high modulus tough layer by cross-linking sodium alginate and acrylamide. Therefore, the present invention studies the dosage of sodium alginate and acrylamide. Preferably, in the high modulus tough layer, the mass ratio of sodium alginate to acrylamide is 0.1:1-1.1.

[0016] In order to ensure the progress of the polymerization reaction, the present invention adds an initiator and a cross-linking agent, and studies the dosage of the two. Preferably, in the high modulus tough layer, the mass ratio of the sodium alginate to the initiator and the cross-linking agent is 0.175:0.01-0.011:0.0015-0.0016.

[0017] Temperature is one of the factors that affect the polymerization reaction time. Generally speaking, an increase in temperature will accelerate the polymerization reaction, thereby shortening the reaction time. However, too high a temperature may also lead to a decrease in product performance or produce side reactions. Therefore, preferably, the polymerization reaction condition is to react at 60°C-65°C for 1.5 h-2 h under sealed conditions.

[0018] The present invention adopts APS to oxidize the hydroxyl groups on the SA main chain into aldehyde groups and carboxyl groups to promote the crosslinking of the modified SA and AM. Therefore, the present invention studies the dosage of the two. Preferably, in the oxidatively modified sodium alginate solution, the mass ratio of sodium alginate to ammonium persulfate is 0.3:0.5-0.6.

[0019] In order to form a low modulus elastic layer, the present invention studies the dosage of each raw material. Preferably, in the elastic layer hydrogel precursor solution, the mass volume ratio of the oxidatively modified sodium alginate solution, acrylamide, water, TA@MXene and the cross-linking agent is 4.9 g-5.0 g: 1.5 g: 2.5 mL: 1 mL: 2.8 mg.

[0020] The present invention does not impose any particular limitation on the type of initiator. Preferably, the initiator is ammonium persulfate.

[0021] The present invention does not impose any particular limitation on the type of the cross-linking agent. Preferably, the cross-linking agent is N,N-methylenebisacrylamide.

[0022] The elastic layer can be obtained by allowing the elastic layer hydrogel precursor solution to react by standing. Therefore, the present invention studies the standing time. Preferably, the standing time is 5 min-8 min.

[0023] Beneficial effects of the present invention

[0024] (1) The sodium alginate-based gradient hydrogel obtained by the present invention has both a wide detection range and high sensitivity, which effectively solves the problem of the inherent conflict between the wide detection range and high sensitivity of SA hydrogel, and is of great significance for expanding the application demand of hydrogel and its application field.

[0025] (2) In the present invention, since the raw materials used in the upper and lower layers contain sodium alginate, the sodium alginate chains in the two layers of hydrogel can interact with each other to produce chain entanglement, making the connection structure of the interface more compact. Therefore, there is an excellent interface layer between the two layers of hydrogel, making it difficult to peel off during use.

[0026] (3) The preparation method of the present invention is simple, practical and easy to promote. Due to the presence of excess APS-induced free radicals in the system during the oxidation process, the upper layer of the gradient hydrogel can be quickly polymerized into a gel within a few minutes, overcoming the shortcomings of the previous layer-by-layer polymerization strategy, such as cumbersome preparation and long time consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0028] Figure 1 These are scanning electron microscope (SEM) images of the hydrogels in Example 1 of the present invention: (a) SEM image of modified SA hydrogel (elastic layer); (b) SEM image of unmodified SA hydrogel (tough layer); (c) SEM image of SA-based gradient hydrogel (gradient layer).

[0029] Figure 2 This is a test of the mechanical properties of the SA-based gradient hydrogel prepared in Example 1 of the present invention: (a) Under manual operation, the SA-based gradient hydrogel can be knotted, twisted and stretched; (b) A real picture of the SA-based gradient hydrogel being pierced by scissors; (c) A real picture of the SA-based gradient hydrogel lifting a 200 g weight.

[0030] Figure 3 The oxidized SA solution was measured by hydroxylamine hydrochloride titration. (a) pH titration test of the oxidized SA solution in Example 1-3, without the addition of hydroxylamine hydrochloride. (b) pH titration test of the oxidized SA solution in Example 1-3, with the addition of hydroxylamine hydrochloride. (c) The difference between the oxidation degree and the volume consumption of sodium hydroxide of the oxidized SA in Example 1-3, where 65°C, 75°C, and 85°C are OSA 65℃ Solution, OSA 75℃ Solution and OSA 85℃ Solution test results.

[0031] Figure 4 These are programmable designs of complex shapes and morphologies of the SA-based gradient hydrogels prepared in Example 4 of the present invention, including (a) rapid multidirectional gel, (b) columnar gel shape, and (c) editable shape.

[0032] Figure 5These are the mechanical property test graphs of the SA-based gradient hydrogel prepared in Example 1 of the present invention, (a) compressive stress-strain curves of the three hydrogels, (b) compressive modulus (left column) and compressive strength (right column) of the three hydrogels, (c) tensile loading and unloading curves of the elastic layer for ten consecutive cycles, 1th represents the first loading-unloading cycle, 2-10th represents the second to tenth loading-unloading cycles, (d) tensile loading and unloading curves of the SA-based gradient hydrogel for ten consecutive cycles, (e) tensile loading and unloading curves of the tough layer for ten consecutive cycles, (f) recovery efficiency of the SA-based gradient hydrogel after continuous loading and unloading cycles, (g) compressive stress-strain curves of the three hydrogels, (h) tensile modulus (left column) and tensile strength (right column) of the three hydrogels, and (i) comparison of the toughness of the three hydrogels.

[0033] Figure 6 is a comparison of the electrical signal output performance of the SA-based gradient hydrogel prepared in Example 1 of the present invention as a sensor, that is, the strain sensing behavior of the three hydrogels, the relative resistance change (ΔR / R 0 ): (a) small strain (5% ~ 40%), (b) large strain (60% ~ 300%).

[0034] Figure 7 The sensitivity and stability test diagram of the SA-based gradient hydrogel prepared in Example 1 of the present invention as a sensor, (a) the relative resistance change (ΔR / R) of the three hydrogels under different tensile strains 0 ) and the corresponding normative coefficient GF, (b) the response and recovery time of SA-based gradient hydrogel; (c) the relative resistance change of SA-based gradient hydrogel when stretched to 50% strain for 500 times.

[0035] Figure 8 The following are the design principle diagrams of the present invention: (a) schematic diagram of the bionic design concept of 3D skin; (b) schematic diagram of the gelation mechanism of the double-layer composite hydrogel. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0037] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0038] In the following examples, a texture analyzer was used to analyze the -1The mechanical properties of the hydrogel were measured at a constant speed. The hydrogel samples were made into standard dumbbell-shaped specimens and cylindrical specimens (20 mm in diameter and 20 mm in height) for tension and compression tests. In the cyclic tensile test, the hydrogel was first subjected to a 60 mm·min -1 The hydrogel was stretched to a fixed strain (100%) at a speed of 100 % and then immediately unloaded at the same speed. The sample was subjected to the next cycle test without waiting. The toughness was obtained by calculating the area under the stress-strain curve. In the cyclic compression test, the sample was first compressed to a predetermined strain (80%) and then unloaded at a constant speed (60 mm min-1) at room temperature. -1 ) Unloading. The loading-unloading compression test was then performed continuously for 10 cycles with no interval between each cycle. The dissipated energy was calculated from the area between the loading-unloading curves. Young's modulus was calculated from the slope of the initial elastic stage of the stress-strain curve.

[0039] In the following examples, a digital source meter (SMU) was used to measure the resistance (R) of a 20.0×10.0×2.0 mm sample of hydrogel. The SMU was combined with a stretching machine to record the resistance signal of the hydrogel sensor during loading and unloading. The real-time signal of the hydrogel sensor under different loading speeds and strains was used to evaluate its sensing performance. Among them, R and R 0 are the real-time resistance and initial resistance of the hydrogel, respectively. The measurement factor (GF) is an important value of the sensor, which is calculated by dividing the relative resistance by the corresponding applied strain.

[0040] Example 1

[0041] A method for preparing SA-based gradient hydrogel, the design principle of which is as follows Figure 8 As shown, the following steps are included:

[0042] First, the delaminated MXene nanosheets were placed in deionized water to form a dispersion (10 mg mL -1 The freshly prepared MXene dispersion was mixed with TA aqueous solution (4 mg mL -1) were mixed at a volume ratio of 1:1 under 600 W ultrasound for 1 h, and vigorously stirred in the dark at room temperature for 15 h to obtain a uniform TA@MXene suspension. Then 0.175 g SA and 1.75 g AM were added to 10 mL deionized water in a beaker. Stir with an electric stirrer until completely dissolved and without bubbles. 10 mg initiator (APS), 1.5 mg cross-linker (MBA), and 0.25 mL TA@MXene suspension were added and stirred at room temperature for 5 min to completely dissolve to obtain a pre-cross-linked acrylamide / sodium alginate solution. The pre-cross-linked acrylamide / sodium alginate solution was then transferred to a mold after removing air with nitrogen and sealed at 65 °C for 1.5 h to obtain a hydrogel. The resulting hydrogel is a tough layer with high modulus. Finally, 0.3 g SA and 0.6 g APS were dissolved in 4.1 g deionized water and stirred in a 75 °C water bath for 25 min to obtain OSA. 75℃ solution, the oxidation degree is 16.5%. 75℃ The solution, 1.5 g AM, 2.5 mL water, 1 mL TA@MXene suspension and 2.8 mg MBA were mixed at high speed to form an elastic layer hydrogel precursor solution, which was quickly poured on the tough layer hydrogel and allowed to stand at room temperature for 5 min to obtain a double-layer composite hydrogel, namely: SA-based gradient hydrogel.

[0043] like Figure 1 As shown, the SA-based gradient hydrogel (referred to as the gradient layer) consists of an elastic layer and a tough layer, wherein the elastic layer is a modified SA hydrogel formed by an elastic layer hydrogel precursor solution, and the tough layer is an unmodified SA hydrogel formed by a pre-cross-linked acrylamide / sodium alginate solution.

[0044] like Figure 2 As shown, under manual operation, the SA-based gradient hydrogel can be knotted, twisted and stretched, is not easily punctured by scissors, and can lift a weight of 200g.

[0045] Example 2

[0046] First, the delaminated MXene nanosheets were placed in deionized water to form a dispersion (10 mg mL -1 The freshly prepared MXene dispersion was mixed with TA aqueous solution (5 mg mL -1) were mixed at a volume ratio of 1:1 under 600 W ultrasound for 1 h, and vigorously stirred in the dark at room temperature for 15 h to obtain a uniform TA@MXene suspension. Then 0.175 g SA and 1.925 g AM were added to 10 mL deionized water in a beaker. Stir with an electric stirrer until completely dissolved and without bubbles. 11 mg initiator (APS), 1.6 mg cross-linker (MBA), and 0.25 mL TA@MXene suspension were added and stirred at room temperature for 5 min to completely dissolve to obtain a pre-cross-linked acrylamide / sodium alginate solution. The pre-cross-linked acrylamide / sodium alginate solution was then transferred to a mold after removing air with nitrogen and sealed at 60 °C for 2 h to obtain a hydrogel. The resulting hydrogel is a tough layer with high modulus. Finally, 0.3 g SA and 0.5 g APS were dissolved in 4.1 g deionized water and stirred in a water bath at 85 °C for 25 min to obtain OSA. 85℃ solution, the oxidation degree is 9.9%. 85℃ The solution, 1.5 g AM, 2.5 mL water, 1 mL TA@MXene suspension and 2.8 mg MBA were mixed at high speed to form an elastic layer hydrogel precursor solution, which was quickly poured on the tough layer hydrogel and allowed to stand at room temperature for 8 min, i.e., SA-based gradient hydrogel.

[0047] Example 3

[0048] First, the delaminated MXene nanosheets were placed in deionized water to form a dispersion (10 mg mL -1 The freshly prepared MXene dispersion was mixed with TA aqueous solution (4 mg mL -1 ) were mixed at a volume ratio of 1:1 under 600 W ultrasound for 1 h, and vigorously stirred in the dark at room temperature for 15 h to obtain a uniform TA@MXene suspension. Then 0.175 g SA and 1.75 g AM were added to 10 mL deionized water in a beaker. Stir with an electric stirrer until completely dissolved and without bubbles. 10 mg initiator (APS), 1.5 mg cross-linker (MBA), and 0.25 mL MXene suspension were added and stirred at room temperature for 5 min to completely dissolve to obtain a pre-cross-linked acrylamide / sodium alginate solution. The pre-cross-linked acrylamide / sodium alginate solution was then transferred to a mold after removing air with nitrogen and sealed at 65 °C for 1.5 h to obtain a hydrogel. The resulting hydrogel is a tough layer with high modulus. Finally, 0.3 g SA and 0.6 g APS were dissolved in 4.1 g deionized water and stirred in a 65 °C water bath for 25 min to obtain OSA. 65℃ solution, the degree of oxidation was 23.1%. 65℃The solution, 1.5 g AM, 2.5 mL water, 1 mL TA@MXene suspension and 2.8 mg MBA were mixed at high speed to form an elastic layer hydrogel precursor solution, which was quickly poured on the tough layer hydrogel and allowed to stand at room temperature for 5 min, i.e., SA-based gradient hydrogel.

[0049] Example 4

[0050] First, the delaminated MXene nanosheets were placed in deionized water to form a dispersion (10 mg mL -1 The freshly prepared MXene dispersion was mixed with TA aqueous solution (4 mg mL -1 ) were mixed at a volume ratio of 1:1 under 600 W ultrasound for 1 h, and stirred vigorously in the dark at room temperature for 15 h to obtain a uniform TA@MXene suspension. Then 0.175 g SA and 1.75 g AM were added to 10 mL of deionized water in a beaker. Stir with an electric stirrer until completely dissolved and without bubbles. Add 10 mg initiator (APS), 1.5 mg cross-linker (MBA), and 0.25 mL TA@MXene suspension, stir at room temperature for 5 min, and completely dissolve to obtain a pre-cross-linked acrylamide / sodium alginate solution. The pre-cross-linked acrylamide / sodium alginate solution was then removed from the air with nitrogen and transferred to customized molds of various shapes (such as Figure 4 As shown), the bottom layer gel was obtained by sealing at 65 °C for 1.5 h. Finally, 0.3 g SA and 0.6 g APS were dissolved in 4.1 g deionized water and stirred in a 75 °C water bath for 25 min to obtain OSA solution. Subsequently, OSA solution, 1.5 g AM, 2.5 mL water, 1 mL TA@MXene suspension and 2.8 mg MBA were mixed at high speed to form an elastic layer hydrogel precursor solution, which was quickly poured on the tough layer hydrogel and allowed to stand at room temperature for 5 min to obtain double-layer composite hydrogels of various shapes.

[0051] The OSA in Examples 1-3 was titrated by hydroxylamine hydrochloride. 75℃ Solution, OSA 85℃ Solution, OSA 65℃ The oxidation degree of the solution is measured, and the test results are as follows Figure 3 shown.

[0052] like Figure 4 As shown, the SA-based gradient hydrogel prepared in Example 1 of the present invention can be programmably designed into a variety of complex shapes and morphologies.

[0053] Depend on Figure 5-Figure 7It can be seen that the modified SA and SA-based gradient hydrogels prepared by the present invention have both the high sensitivity of the modified SA-based hydrogel (elastic layer) and the wide detection range of the unmodified SA-based hydrogel (tough layer). The GF reaches 1.01 under small strain (0-50%) and 3.51 under large strain (100-200%). In different monitoring ranges, they maintain high sensitivity, which well solves the inherent conflict between the detection range and sensitivity of the existing homogeneous hydrogel. The constructed sensor has stable and excellent output performance, creating favorable conditions for the development of flexible wearable electronic devices.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a sodium alginate-based gradient hydrogel sensor, characterized in that: include: The MXene dispersion and the tannic acid aqueous solution were mixed evenly to obtain a TA@MXene suspension; Sodium alginate and acrylamide are dissolved in a solvent, added into the TA@MXene suspension and mixed evenly, and a polymerization reaction is carried out in the presence of an initiator and a cross-linking agent to obtain a tough layer with a high modulus. allowing sodium alginate and ammonium persulfate to react in a solution to obtain an oxidatively modified sodium alginate solution; The oxidatively modified sodium alginate solution is uniformly mixed with acrylamide, water, a crosslinking agent and a TA@MXene suspension to obtain an elastic layer hydrogel precursor solution; The elastic layer hydrogel precursor solution is placed on the high modulus tough layer and allowed to stand to obtain a sodium alginate-based gradient hydrogel sensor.

2. The method for preparing the sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: In the TA@MXene suspension, the mass ratio of MXene to tannic acid is 10:4-5.

3. The method for preparing the sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: In the high modulus tough layer, the mass ratio of sodium alginate to acrylamide is 0.1:1-1.

1.

4. The method for preparing the sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: In the high modulus tough layer, the mass ratio of the sodium alginate to the initiator and the cross-linking agent is 0.175:0.01-0.011:0.0015-0.0016.

5. The method for preparing the sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: The polymerization reaction conditions are as follows: reacting at 60° C.-65° C. for 1.5 h-2 h under sealed conditions.

6. The method for preparing the sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: In the oxidatively modified sodium alginate solution, the mass ratio of sodium alginate to ammonium persulfate is 0.3:0.5-0.

6.

7. The method for preparing a sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: In the elastic layer hydrogel precursor solution, the mass volume ratio of the oxidatively modified sodium alginate solution, acrylamide, water, TA@MXene and the cross-linking agent is 4.9 g-5.0 g: 1.5 g: 2.5 mL: 1 mL: 2.8 mg.

8. The method for preparing a sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: The initiator is ammonium persulfate.

9. The method for preparing a sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: The cross-linking agent is N,N-methylenebisacrylamide.

10. The method for preparing a sodium alginate-based gradient hydrogel sensor according to claim 1, characterized in that: The standing time is 5 min-8 min.

Citation Information

Patent Citations

  • Preparation method of ionized water gel with gradient structure as well as product and application of ionized water gel

    CN115181290A

  • Dual-network gradient gel for 3D printing and preparation method and application thereof

    CN117467163A